THE INCREASED INCIDENCE OF NAUSEA AND VOMITING DUE TO ANXIETY IN PACLITAXEL CARBOPLATIN CHEMOTHERAPY IN A 48 YEARS OLD FEMALE PATIENT WITH CERVICAL CANCER: A Case Report - Putra, I. F. W.; Noviyani, R.; Suwiyoga, and, K. (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2014)
Nausea and vomiting was the frequently side effects in chemotherapy.Uncontrolled nausea and vomiting can cause weakened body condition, reduced appetite and drinking, dehydration, electrolyte disturbances, reduced nutritional status so the patient refused to undergo further chemotherapy. Anxiety is one of the factors that increase the risk of nausea and vomiting. We reported the case of the woman 48 years old, height 150 cm, weight 51 kg, occupation housewife, diagnosed non-keratinizing squamous cell carcinoma cervical cancer  stage-IIB and received paclitaxel carboplatin for three cycles of chemotherapy. She experienced anxiety, acute nausea vomiting on the third cycle of chemotherapy and delayed nausea and vomiting of the three cycles of chemotherapy.
Keywords: cervical cancer, chemotherapy, nausea, vomiting, anxiety